IMPLEMENTATION OF SECURITY IN DYNAMIC BINARY TRANSLATION - Hariyanto Hariyanto Hariyanto (JAKSTIK Journal, 2004)
Computers at this time is not an expensive item that only owned by a group of people, but itis a tool that can help in completing one's work. It is worth a secure and protect their datafrom data-interference and virus attacks coming from inside and outside the system. At theend of computer security will play an important role in data security.A dynamic binary translation is a dynamic system in the machine code fragment damage thatmay directly or enclosed diesekusi interpreter software. When mengesekusi interpreters, thestatistics are collected to determine how often these fragments diesekusi and how often takenbranches. Fragments of the most frequently used and transformed in the cache for subsequentexecution. Once the fragment is in the cache, they may be merged with other fragments whenthey were found separately by direction of an unconditional branch. This architecture is usedfor optimizing the dynamic programs, instruments and translational arsitetur intropeksi